Pancreatic cancer in a Non-Tertiary Center: CEA and Bilirubin More Predictive than CA 19-9 at Initial Presentation - Al Masri Majd; Imam Adnan; Popover Jesse; Mackey Alexandra; King Natalie; Kalathia Chris; Toomey Paul (Journal of Pancreas, 2025)
Background This study was undertaken to delineate the most predictive pattern at presentation for patients with non-metastatic pancreatic cancer compared to patients with metastatic pancreatic cancer who present to a medium sized hospital. Methods Data were collected at a medium sized hospital from 2009-2014 for patients with newly diagnosed pancreatic adenocarcinoma. Laboratory values, CT scans, pathology reports and ERCP results were obtained. Data are presented as mean (median +/- standard deviation). Results Fifty-two patients met the criteria for inclusion and were clinically diagnosed with pancreatic cancer. The median age was 71 years old. CEA levels for metastatic pancreatic cancer were 107.9 (20.6 +/- 166.7) ng/dl and 9 (6 +/- 11.6) ng/dl for non-metastatic cancer (P-value<0.05). Bilirubin levels for metastatic pancreatic cancer were 4.1 (0.7 +/- 6.6) mg/dl and 10.3 (10.4 +/- 8.1) mg/dl for non-metastatic cancer (p=0.009). CA19-9 levels for metastatic pancreatic cancer were 37,529 (644 +/- 88,352) U/ml and 5,150 (668 +/- 16,985) U/ml for non-metastatic cancer. Conclusion Elevated total bilirubin alongside low CEA appears to be a stronger predictor of non-metastatic disease at presentation compared to CA 19-9 alone.
Keywords: Pancreas